Assessment of Double Modulation Pyrometry as a diagnostic tool for use in concentrated solar facilities. (1st November 2018) - Potamias, Dimitrios; Alxneit, Ivo; Sans, Jean-Louis; Guillot, Emmanuel; Wokaun, Alexander
Highlights: Performance of double modulation pyrometry is demonstrated in a traditional solar furnace. Comparison of results to a reference solar blind pyrometer is reported. On-line measurement of the emissivity allows the method to cope with dynamically changing optical properties of the sample. Abstract: Double modulation pyrometry (DMP) is a pyrometric method developed to enable radiometric temperature measurements in solar simulators, where solar blind pyrometry cannot be applied due to the continuous spectrum of the artificial light source. Sofar, DMP has been characterized in two solar simulator facilities, but no direct comparison to a reference pyrometer has been performed until now due to the limitations of applying pyrometry in solar simulators. Here, a series of experiments is reported that were conducted in concentrated natural sunlight where reference pyrometers are available. They demonstrate the performance enhancement gained by utilizing the inherent advantages of DMP, i.e. the in-situ reflectance measurement and the freedom to select the operation wavelength.